Severe mental illness is associated with increased mortality and severe course of COVID‐19. (13th May 2021) - Barcella, Carlo Alberto; Polcwiartek, Christoffer; Mohr, Grimur Høgnason; Hodges, Gethin; Søndergaard, Kathrine; Niels Bang, Casper; Andersen, Mikkel Porsborg; Fosbøl, Emil; Køber, Lars; Schou, Morten; Torp‐Pedersen, Christian; Kessing, Lars Vedel; et al.
Abstract: Objective: Psychiatric disorders have been associated with unfavourable outcome following respiratory infections. Whether this also applies to coronavirus disease 2019 (COVID‐19) has been scarcely investigated. Methods: Using the Danish administrative databases, we identified all patients with a positive real‐time reverse transcription‐polymerase chain reaction test for COVID‐19 in Denmark up to and including 2 January 2021. Multivariable cox regression was used to calculate 30‐day absolute risk and average risk ratio (ARR) for the composite end point of death from any cause and severe COVID‐19 associated with psychiatric disorders, defined using both hospital diagnoses and redemption of psychotropic drugs. Results: We included 144, 321 patients with COVID‐19. Compared with patients without psychiatric disorders, the standardized ARR of the composite outcome was significantly increased for patients with severe mental illness including schizophrenia spectrum disorders 2.43 (95% confidence interval [CI], 1.79–3.07), bipolar disorder 2.11 (95% CI, 1.25–2.97), unipolar depression 1.70 (95% CI, 1.38–2.02), and for patients who redeemed psychotropic drugs 1.70 (95% CI, 1.48–1.92). No association was found for patients with other psychiatric disorders 1.13 (95% CI, 0.86–1.38). Similar results were seen with the outcomes of death or severe COVID‐19. Among the different psychiatric subgroups, patients with schizophrenia spectrum disorders had the highest 30‐day absolute risk for the composite outcome 3.1% (95% CI, 2.3–3.9%), death 1.2% (95% CI, 0.4–2.0%) and severe COVID‐19 2.7% (95% CI, 1.9–3.6%). Conclusion: Schizophrenia spectrum disorders, bipolar disorder, unipolar depression and psychotropic drug redemption are associated with unfavourable outcomes in patients with COVID‐19.